Kinerja Keuangan pada Kantor Pusat KSP Kopdit Pintu Air Rotat Ditinjau dari ROI, ROA dan ROE - Maria Viviana Nurak Lewar; Maria Goreti Mao Tokan; Yoseph Darius Purnama Rangga (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine the effect of ROA, ROE and ROI on financial performance. There are three independent variables, namely ROA, ROE and ROI, and the dependent variable is financial performance. The method used in this study is quantitative in associative form. The type of data in this study is time series data with a time period from 2016-2020. The source of financial statement data was obtained from the Head Office of KSP Kopdit Pintu Air Rotat. The analysis technique applied to this study is multiple linear regression. The analysis tool used is SPSS V.22. The results showed that the variable ROI, ROA and ROE had a positive and significant effect on profit growth. This is indicated by significant values of 0.004, 0.003 and 0.000 smaller than 0.05. While simultaneously ROI, ROA, and ROE have a positive and significant effect on profit growth with a significant value of 0.000.